2017
DOI: 10.1016/j.physbeh.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of social behavior directed toward sick partners and its relation to central cytokine expression in rats

Abstract: Acute illness not only reduces the expression of social behavior by sick rodents, but can also lead to avoidance responses when detected by healthy, would-be social partners. When healthy animals interact with a sick partner, an intriguing question arises: does exposure to a sick conspecific elicit an anticipatory immune response that would facilitate defense against future infection? To address this question, healthy adult male Sprague-Dawley rats (N=64) were given a brief social interaction (30 min) with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…The roles of other neuromodulators, including immune components that can affect behaviour and are influenced by oestrogens, and pathogen threat also need to be further considered. Results of recent studies have indicated that male rats exposed to LPS-treated conspecifics display avoidance responses and a modest increase in the cytokine tumour necrosis factor a [133]. This avoidance is consistent with activation of the behavioural immune system, the display of disgust and associated cognitive responses.…”
Section: (B) Oestrogens Pathogen Avoidance and Social Cognitionmentioning
confidence: 62%
“…The roles of other neuromodulators, including immune components that can affect behaviour and are influenced by oestrogens, and pathogen threat also need to be further considered. Results of recent studies have indicated that male rats exposed to LPS-treated conspecifics display avoidance responses and a modest increase in the cytokine tumour necrosis factor a [133]. This avoidance is consistent with activation of the behavioural immune system, the display of disgust and associated cognitive responses.…”
Section: (B) Oestrogens Pathogen Avoidance and Social Cognitionmentioning
confidence: 62%
“…The transmission of affect allows for the communication of impending threat between conspecifics [ 2 ] and exposure to a stressed animal alters the physiological state and behavior of an observer [ 3 ]. Observers may appraise situations to make decisions that can either protect them from harm, such as avoiding a sick or aggressive individual [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These protective responses in humans have been coined as the “behavioral immune system” and are associated with the elicitation of anticipatory neuroimmune responses, appropriate affective and cognitive responses, and relevant avoidance responses that may be the initial defense against pathogens. Similar aversive and avoidance responses to parasites and pathogens are evident in non‐human animals and have similarly been interpreted as reflecting disgust and perhaps a comparable behavioral immune system . Although not explicitly stated these aversive and avoidance may be considered in the context of a behavioral immune system.…”
Section: Social Cognition Disgust and Pathogen Avoidancementioning
confidence: 93%
“…Similar aversive and avoidance responses to parasites and pathogens are evident in non-human animals and have similarly been interpreted as reflecting disgust and perhaps a comparable behavioral immune system. 16,24,25 Although not explicitly stated these aversive and avoidance may be considered in the context of a behavioral immune system.…”
Section: Social Cognition Disgust and Pathogen Avoidancementioning
confidence: 99%